Left- versus right-sided hepatectomy with hilar en-bloc resection in perihilar cholangiocarcinoma. Issue 3 (March 2020) - Bednarsch, Jan; Czigany, Zoltan; Lurje, Isabella; Tacke, Frank; Strnad, Pavel; Ulmer, Tom F.; Gaisa, Nadine T.; Bruners, Philipp; Neumann, Ulf P.; Lurje, Georg
Abstract: Background: Major liver resections with portal vein resection (PVR) have emerged as the preferred treatment for patients with perihilar cholangiocarcinoma (pCCA). Whether the resection of the liver should be preferably performed as left- (LH) or right-sided hepatectomy (RH) with or without hilar en-bloc technique is still subject of ongoing debate. Methods: Between 2011 and 2016, 91 patients with pCCA underwent surgery in curative intent at our institution. Perioperative, pathological and survival data from all consecutive patients undergoing hilar en-bloc resection for pCCA were analyzed retrospectively. Patients undergoing hepatoduodenectomy (n = 8) or ALPPS (Associating liver partition and portal vein ligation for staged hepatectomy) (n = 2) were excluded from the analysis. Results: Tumor grading, microvascular invasion, lymphovascular invasion, N-category, T-category, R-status and UICC-tumor staging were similar in the RH (n = 45) and LH (n = 36) groups. Perioperative morbidity and mortality were higher after RH compared to LH (mortality: 15.6% (7/45) vs. 8.3% (3/36) p = 0.003). Three-year (62% vs. 51%) and the 5-year OS (30% vs. 46%) were comparable between LH and RH groups respectively (p = 0.519, log rank). Conclusions: The present study supports the concept of surgically aggressive therapy in pCCA. LH and RH hilar en-bloc resection demonstrate a comparable long-term survival, suggesting that LH hilar en-bloc resections are feasible and safe in high-volume centers.